Hubungan Tingkat Pengetahuan Dengan Sikap Lansia Dalam Mengatasi Kekambuhan Penyakit Reumatik Di Wilayah Kerja Puskesmas Kecamatan Pidie Kabupaten Pidie - Risna, Risna; Fauzia, Neila; Riska, Cut (Teewan Journal Solutions, 2024)
Elderly knowledge is one of the aspects that impact the maturation of healthy attitudes. Attitude formation requires time, and consequently, developments, as they comprehend, could affect rheumatic disease recurrence. The research aimed to determine the correlation between the levels of elderly knowledge and attitudes in preventing rheumatism occurrence at the Pidie Public Health Center Area, Pidie. The type of research was analytic through a cross-sectional design. This research was conducted from July 3rd to July 19th, 2024. The population in the research was the elderly, which consisted of 326 people. 77 respondents were taken as samples by using the random sampling method. To obtain the data, the researcher used a questionnaire sheet. The result showed 43 respondents (55,8%) had negative attitudes toward the elderly in preventing rheumatism occurrence. It found 50 respondents (64,9%) with sufficient knowledge of the elderly in preventing rheumatism occurrence. In brief, there was a correlation between the levels of elderly knowledge and attitudes toward preventing rheumatism, obtaining a P-value of 0.000 ≤ 0.05. Therefore, the researcher expected that health workers should properly increase their health services for the elderly by monitoring their lifestyle to prevent rheumatism.